DETERMINAN FINANCIAL STATEMENT FRAUD PADA BUMN TERDAFTAR DI BURSA EFEK INDONESIA - Bob Mustafa; Elsa Sari Yuliana; Wahyudi (Bajang Institute, 2024)
This research aims to obtain empirical evidence regarding the influence of pentagon fraud as proxied by ROA, Ineffective Monitoring, Change in Auditor, Change in Board of Directors, and Frequent Number of CEO's Picture on Financial Statement Fraud using the F-Score Model in listed state-owned companies on the Indonesian Stock Exchange 2016-2018. This research is a quantitative research that uses a population of state-owned companies listed on the IDX during 2016-2018. The sampling method used purposive sampling with a total sample of 14 state-owned companies. This research uses panel data regression analysis. The research results show that partially, ROA, Ineffective Monitoring, Change in Auditor, Change in Board of Director, Frequent Number of CEO's Picture do not have a significant influence on the Financial Statement Fraud variable. Simultaneous testing also shows the same results, that ROA, Ineffective Monitoring, Change in Auditor, Change in Board of Directors, Frequent Number of CEO's Picture do not have a significant influence on the Financial Statement Fraud variable. It means,These five variables are not able to detect potential fraud that occurs instate-owned company.